Health Education Through Video Animation to Primigravida Mother's Readiness in Childbirth - Emi Sutrisminah; Suryo Ediyono; Endang Susilowati; Siti Suhartinah (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Labor is the process of opening and thinning the cervix and the fetus descending into the birth canal. Readiness in facing labor is one of the indicators of the successful labor process. There are four things that need to be prepared before experiencing childbirth such as physical, psychological, financial, and cultural readiness. Primigravidas often have disturbing thoughts when facing labor and mostly bear difficulties in preparing for childbirth due to their lackness of birth experience. This study aimed to determine the effect of health education through audio-visual media on readiness when facing childbirth for primigravidas. This research used a pre-experimental study with one group pretest and posttest design. The research sample included 43 primigravidas in the third trimester taken by total sampling. The research instrument used was a questionnaire and analyzed by using paired t-test. This study showed that there was a significant difference in the readiness of primigravidas when facing childbirth (p-value=0,000) before and after being given health education through animated videos. Health education through animated video media for childbirth preparation is one way that can be applied to provide health education to primigravidas. Based on the results, it is recommended that health education through animated videos for childbirth preparation be used to increase the readiness of mothers in facing childbirth.